Evaluation of the Normative Framework of Strategic Planning for the Realization of Good Urban Governance in Tehran\'s 22 District - Mansor Azizi; Rasol Darskhan; Mohamadreza Poormohamadi (تحقیقات کاربردی علوم جغرافیایی)
The Urban Development Strategy Plan is an attempt to take into account the potential and talent capacities of the city in an institutionalized and systematic framework and the construction of a clear future as one of the current concerns that identifies strategies for creating urban sustainability conditions in good governance. The main idea of ​​this policy is that it is imperative for all cities in an increasingly competitive and increasingly global economy to have a clever and clear strategy for how its land is positioned to minimize negative effects, predict potential shocks, and exploit the comparative potential and Competitive In such a situation, making decisions for urban issues and planning for the future is much more difficult. The purpose of this study is to evaluate the urban development strategy of District 22 as one of the tools for implementing urban governance paradigm. The research method is descriptive-analytic. The tool for evaluating AHP's hierarchical analysis technique is implemented according to the views of the experts and stakeholders. The results of the research indicate a significant difference between the design of CDS and its implementation phase.